Continuous measurement of reticuloruminal pH values in dairy cows during the transition period from barn to pasture feeding using an indwelling wireless data transmitting unit. Issue 2 (30th September 2014) - Gasteiner, J.; Horn, M.; Steinwidder, A.
Summary This study was performed to investigate the effect of the transition from barn feeding to pasture on the pattern of reticuloruminal pH values in 8 multiparous dairy cows. A indwelling wireless data transmitting system for pH measurement was given to 8 multiparous cows orally. Reticuloruminal pH values were measured every 600 s over a period of 42 days. After 7 days of barn feeding (period 1), all of the animals were pastured with increasing grazing times from 2 to 7 h/day over 7 days (period 2). From day 15 to day 21 (period 3), the cows spent 7 h/day on pasture. Beginning on day 22, the animals had 20 h/day access to pasture (day and night grazing). To study reticuloruminal adaptation to pasture feeding, the phase of day and night grazing was subdivided into another 3 weekly periods (periods 4–6). Despite a mild transition period from barn feeding to pasture, significant effects on reticuloruminal pH values were observed. During barn feeding, the mean reticuloruminal pH value for all of the cows was 6.44 ± 0.14, and the pH values decreased significantly (p < 0.001) during period 2 and 3 to 6.24 ± 0.17 and 6.21 ± 0.19 respectively. During periods 4, 5 and 6, the reticuloruminal pH values increased again (pH 6.25 ± 0.22; pH 6.31 ± 0.17; pH 6.37 ± 0.16). Our results showed that the animals had significantly lowered reticuloruminal pH during the periods of feed transition from barn to pasture feeding. Despite these significant changes, the decrease was not harmful, as indicated by data of feed intake and milk production.